Deep infection after hip hemiarthroplasty: risk factors for infection and outcome of treatments. (2021) - Craxford, S.; Marson, B. A.; Nightingale, J.; Ikram, A.; Agrawal, Y.; Deakin, D.; Ollivere, B.
No abstract available